The Relationship Between Islamic Hygiene Practices in Children With TheIncidence of Soil Transmitted Helminth in Makassar - N, Fattah; A I, Arfah; A H, Esa; Rasfayanah, -; Z, Salsabila (International Journal of Human and Health Sciences (IJHHS), 2024)
Objective: Soil Transmitted Helminth (STH) is a helminthic infectious disease whose mode of transmission is through the soil. Personal hygiene or individual hygiene can be interpreted as a person's efforts to maintain their personal hygiene. The better the parenting style carried out by the parents, the less likely the child will be infected, and vice versa. The purpose of this research is to find out the relationship between parenting styles according to an Islamic perspective in building children's personal hygiene with the incidence of STH infection. Methods: The research used analytical research, with a cross-sectional study design. The data collection technique is by filling out questionnaires and examining the feces samples. And using Fisher's Exact Test analysis Result: Based on the research, the forty-three samples where thirty-three children were infected with worms, which accounts for 76.7% of the total. Meanwhile, ten children were not infected with worms, making up 23.3% of the sample. When considering age characteristics, it was found that 5-year-olds were the most affected by worm infections, with a percentage of 46.5%. Among the children, 39.5% of girls were infected with worms, while 37.2% of boys had worm infections. From 43 samples in this study, there was a relationship between the habit of ablution with the incidence of helminthiasis (p: 0.027), there was a relationship between hand and foot hygiene and the incidence of worms where (p:0.020), there was a relationship between eating habits with the incidence of worms where (p: 0.034). In this study, there was no significant relationship between cleanliness of skin and clothing with the incidence of worms (p: 0.613), bowel habits and nail hygiene with the incidence of worms (p: 0.226), and oral hygiene with the incidence of worms where (p:0.145). Conclusion: There is a relationship between parenting according to an Islamic perspective in building children's personal hygiene with the incidence of STH. International Journal of Human and Health Sciences Supplementary Issue 01: 2024 Page: S63